(untitled) (Journal of Universal Science Research, 2025)
This research paper in translation investigates domestication and foreignization as primary two methods which maintain the uniqueness of a text for the target audience and how these two strategies can be applied in the translation of short stories in order to make it valuable material to explore inclusive cross-cultural understanding. Concerning cultural and ideological values within historical and social factors, this research work covers foreign elements which are pivotal in the comprehension of how cultural adaptation functions in translation.